Coleon U, Isolated from Plectranthus mutabilis Codd., Decreases P-Glycoprotein Activity Due to Mitochondrial Inhibition - Jovanović Stojanov, Sofija (2023)
Multidrug resistance in cancer is often mediated by P-glycoprotein. Natural compounds have been suggested as a fourth generation of P-glycoprotein inhibitors. Coleon U, isolated from Plectranthus mutabilis Codd., was reported to modulate P-glycoprotein activity but the underlying mechanism has not yet been revealed. Therefore, the effects of Coleon U on cell viability, proliferation, and cell death induction were studied in a non-small-cell lung carcinoma model comprising sensitive and multidrug-resistant cells with P-glycoprotein overexpression. P-glycoprotein activity and mitochondrial membrane potential were assessed by flow cytometry upon Coleon U, sodium-orthovanadate (an ATPase inhibitor), and verapamil (an ATPase stimulator) treatments. SwissADME was used to identify the pharmacokinetic properties of Coleon U, while P-glycoprotein expression was studied by immunofluorescence. Our results showed that Coleon U is not a P-glycoprotein substrate and is equally efficient in sensitive and multidrug-resistant cancer cells. A decrease in P-glycoprotein activity observed with Coleon U and verapamil after 72 h is antagonized in combination with sodium-orthovanadate. Coleon U induced a pronounced effect on mitochondrial membrane depolarization and showed a tendency to decrease P-glycoprotein expression. In conclusion, Coleon U-delayed effect on the decrease in P-glycoprotein activity is due to P-glycoprotein's functioning dependence on ATP production in mitochondria.